(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
This paper explores the repercussions of the COVID-19 pandemic on the banking sector, focusing on the escalation of credit risk and its effects on non-performing loans (NPLs), loan loss provisions, and economic activity in the Republic of Kosovo. Amidst the global health crisis, the banking industry faced heightened risk, resulting in increased NPLs, heightened loan loss provisions, and diminished economic operations throughout 2020. Despite these challenges, the sector demonstrated resilience by adhering to governmental guidelines for credit provision, which offered mutual benefits to customers and banks alike. The study highlights the adverse impacts experienced during the peak of the pandemic, alongside the subsequent recovery and improvements in the banking and macroeconomic sectors by the end of 2021. Through the use of multiple linear regression analysis, incorporating a COVID-19 dummy variable, the paper investigates the pandemic’s impact on the banking sector’s stability and its correlation with economic activities. This analysis aims to provide insights into the dynamics between the pandemic crisis and its influence on financial stability through the lens of NPLs, offering valuable implications for policymakers and financial institutions in mitigating similar future risks.